CEUS Time Intensity Curves in the Differentiation Between Leydig Cell Carcinoma and Seminoma: A Multicenter Study - Drudi, F. M.; Valentino, M.; Bertolotto, M.; Malpassini, F.; Maghella, F.; Cantisani, V.; Liberatore, M.; De Felice, C.; D'Ambrosio, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: Ultrasound (US) is the main imaging technique in the assessment of testicular masses, as it has proved to be highly accurate in the visualization of these pathologies. Identification of a Leydig cell tumor is essential since the lesion is benign in 90 % of cases. The aim of this multicenter study is to assess the effectiveness of contrast-enhanced ultrasound (CEUS) in differentiating Leydig cell tumors from seminoma using qualitative and quantitative features.Materials and Methods: From February 2011 to December 2013, 31 patients (mean age: 34 years; range: 25 – 52) were recruited for this prospective study. Three of them were monorchid. Therefore, a total of 59 testicles were assessed. All patients underwent grayscale US, color Doppler ultrasound (CDUS), CEUS and orchiectomy. The paired one-tailed Student‘s t-test was carried out to differentiate between Leydig cell tumors and seminomas.Results: 31 lesions suspicious for malignancy were hypoechoic on grayscale US while they did not show a typical pattern on CDUS. CEUS qualitative analysis, based on contrast enhancement pattern, during the arterial and venous phases, did not allow discrimination of Leydig cell tumors from seminoma. Quantitative analysis of time-intensity curves (TICs) demonstrated that only three parameters presented statistical significance, i. e. wash-in rate (WiR) p = 0.014, peak enhancement (PE) p = 0.001 and time to peak (TTP) p = 0.003.Conclusion: The vascular bed of a Leydig cell tumor is wider and the blood flow velocity is higher than that of a seminoma due to more regular neovascularization. In contrast, a seminoma presents large areas of necrosis due to irregular neovascularization. This explains the different PE and WiR values. Further studies involving larger patient populations are mandatory to confirm these encouraging preliminary results.
Keywords: scrotum; seminoma; tumor; ultrasound; CEUS